The contribution of foreign languages in the development of enterprises: a review of literature - Delplancq, Véronique (2018)
Foreign languages have been the subject of research due to their importance as a means of communication. In fact, the competitiveness of companies is, nowadays, influenced in part by the communication resulting from their contact with companies from different countries, which requires a thorough knowledge of the language of these countries. On the other hand, for the success and progression of workers, it is crucial they acquire and develop foreign language skills. In this context, there have been multiple efforts by the European Commission to promote language learning in Europe and worldwide. In fact, over the past few years, several studies have demonstrated the need of companies to value foreign language skills among workers and collaborators. Multilingualism becomes, therefore, increasingly fundamental to the growth of the economic power of companies, and the competence in foreign languages can be the key factor to enter the labour market. Thus, the present study aims to understand the importance of foreign languages in the development of enterprises and their workers. The research question underlying the review of literature is: “What is the perception of companies regarding the importance of foreign languages for their economic progression and for their workers? To answer this research question, a review of the literature was conducted taking into consideration documents, reports and other secondary sources. For the collection of scientific evidence, research was carried out in the following databases: Science Direct from Elsevier; PubMed; B-on; Google Scholar and in the RCAAP portal. We used as descriptors of our search the following terms: industry, foreign language, multilingualism, higher education, employment, enterprise, among others.